Fungos Micorrízicos Arbusculares em Camadas Orgânicas do Solo da Amazônia - Braga, João Gabriel Barbosa (2020)
The Amazon attracts great attention from the international scientific community for being one of the main biodiversity centers on the planet. Despite its high plant diversity, this biome is located in a region where soils of low fertility predominate. Much of the biomass and energy stored by these plants are lost to the decomposing systems present in the soil, thus maintaining an organic layer of high relevance for the maintenance of plant nutrition. The maintenance of this ecosystem would be impossible without the presence of microorganisms that transform and enrich the so-called humus forms. Among them are the arbuscular mycorrhizal fungi (AMF), whose diversity and abundance are directly related to the diversity and production of forest systems. Despite having been the subject of several studies, little is known about the dynamics of microbial communities in humus forms in the Amazon, mainly because of their importance in this unique ecosystem. Thus, this work aimed to assess the diversity of AMF in a forest fragment in the eastern Amazon and an adjacent pasture, relating the AMF diversity with the vertical distribution of organic matter. Additionally, mycoheterotrophic plants were collected, and the AMF associated with their roots and those of adjacent plants were evaluated. The samples were collected in the city of Baião (PA). Five points, 50 m apart, were collected along a transect in the forest and pasture. The forest floor was stratified into seven layers, from the litter to the underlying A horizon. In the pasture, three layers were collected, including the mineral soil. The mineral portion of the soils and the organic layers that contained roots were used to prepare trap cultivation pots with Uruchloa decumbens. After the multiplication of fungi and obtaining viable spores, the fungi were identified based on their morphological and molecular characters. No difference in the composition of species of AMF species between the layers and the land-use systems evaluated. However, the highest concentration of glomalin was observed in the FH, H1, and H2 layers of the forest, which are characterized by being rich in thin roots and, therefore, as infection sites for AMF. The mycoheterotrophic plant was classified as Voyriella parviflora. Only two species, one of the genus Glomus and the other, of Racocetra, were associated with V. parviflora, indicating that this plant selects these species among the others existing in the roots of the surrounding autotrophic plants.